Identities in the Era of Globalisation - Markéta Sedláková; David Košatka (Charles University, 2022)
Aims: This article analyses the reflections of a range of student teachers on their international experiences for their impact on the students' personality, comfort, and effectiveness in diverse environments. We will describe the process of identity formation during the time that student teachers are exposed to such environments. We see international experience and raising awareness of diversity as a personal and social developmental part of their professional preparation.This may be seen as contributing to the transformation of the school climate towards inclusive and culturally responsive education. Methods: The main research question was how the internationalisation of education enhances student teachers' cultural sensitivity to diversity. The qualitative investigation focuses on aspects of the international experience of student teachers concerning teaching practice. Ten semi-structured interviews with student teachers who have had international experience provided the data. Findings: Experiencing different socio-cultural environments, we found, impacts on the construction of multiple/hybrid identities and engenders empathy for diversity. The implications for inclusive practice were identified, including reflective teaching strategies, the development of culturally sensitive attitudes, and awareness of others' perspectives and cultural habits. Conclusion: A positive benefit for student teachers from grasping and understanding diversity in such an environment is the enhancement of the effectiveness of teaching. The internationalisation of the curriculum expands the student teachers' responsiveness.